Resveratrol Mitigates Gold Nanoparticle-Induced Nephrotoxicity via Modulation of Oxidative Stress and Inflammation in Mice - Alhamadani, Mohammed; Jarad, Ahmed S.; El-Sayed, Wael M. (American Journal of Biology and Natural Sciences, 2025)
Gold nanoparticles (AuNPs) hold promise for biomedical applications but raise safety concerns, particularly nephrotoxicity linked to oxidative stress, inflammation, and apoptosis. Resveratrol (RSV), a natural polyphenol with antioxidant and anti-inflammatory properties, may mitigate these adverse effects, yet its renoprotective role against AuNP-induced injury remains underexplored. Male mice (n = 30) were randomly assigned to three groups: control, AuNPs (8 mg/kg/day), and AuNPs + RSV (15 mg/kg/day). Treatments were administered orally for 14 days. Body and kidney weights were recorded, and renal tissues were analyzed for tumor necrosis factor-α (TNF-α), caspase-3, reduced glutathione (GSH), superoxide dismutase (SOD), and catalase (CAT). Data were analyzed using ANOVA with Tukey–Kramer post hoc testing. AuNP exposure significantly increased final body weight (30%) and relative kidney weight (92%) compared with controls (P < 0.05). RSV co-treatment prevented weight gain and attenuated kidney hypertrophy, reducing values to near-control levels. AuNPs markedly elevated renal TNF-α and caspase-3 activity, while RSV co-treatment normalized both markers. Similarly, AuNPs depleted renal GSH, SOD, and CAT, whereas RSV significantly restored these antioxidant defenses, though not fully to control levels. Histopathological analysis confirmed severe glomerular and tubular injury in the AuNP group, which was markedly alleviated by RSV pretreatment. AuNPs induce renal hypertrophy, oxidative stress, inflammation, apoptosis, and structural damage in male mice. RSV co-treatment substantially mitigates these biochemical and histopathological alterations through antioxidant, anti-inflammatory, and anti-apoptotic mechanisms, supporting its potential as a protective adjuvant in nanomedicine.